2002
DOI: 10.1104/pp.006783
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Plants Ectopically Expressing Arabidopsis CBF1 Show Enhanced Resistance to Water Deficit Stress

Abstract: A DNA cassette containing an Arabidopsis C repeat/dehydration-responsive element binding factor 1 (CBF1) cDNA and a nos terminator, driven by a cauliflower mosaic virus 35S promoter, was transformed into the tomato (Lycopersicon esculentum) genome. These transgenic tomato plants were more resistant to water deficit stress than the wild-type plants. The transgenic plants exhibited growth retardation by showing dwarf phenotype, and the fruit and seed numbers and fresh weight of the transgenic tomato plants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
201
3
15

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 381 publications
(231 citation statements)
references
References 33 publications
12
201
3
15
Order By: Relevance
“…Although OE-OsMYB3R-2 exhibited enhanced cold tolerance in rice, it also resulted in growth retardation under normal conditions [42]. Similarly, OE-DREB1A in Arabidopsis caused severe growth retardation [41], and overexpression of CBF1 in tomato resulted in a dwarf phenotype [43]. These results indicate that constitutive activation of stress-responsive genes increases stress tolerance but may also result in growth retardation.…”
Section: Discussionmentioning
confidence: 96%
“…Although OE-OsMYB3R-2 exhibited enhanced cold tolerance in rice, it also resulted in growth retardation under normal conditions [42]. Similarly, OE-DREB1A in Arabidopsis caused severe growth retardation [41], and overexpression of CBF1 in tomato resulted in a dwarf phenotype [43]. These results indicate that constitutive activation of stress-responsive genes increases stress tolerance but may also result in growth retardation.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, we have demonstrated that constitutive expression of AtCBF1 in tomato increased tolerance to chilling and water deficit (Hsieh et al, 2002a(Hsieh et al, , 2002b. To identify the genes that were differentially expressed in AtCBF1 transgenic tomato plants, we now used subtractive hybridization and homemade microarray systems (Liu et al, 2006).…”
Section: Several Pathogenesis-related Genes Are Activated In Cbf1 Tramentioning
confidence: 99%
“…Thus, we conclude that constitutive expression of AtCBF1 in transgenic tomato enhances BW resistance by systemic suppression of internal bacterial multiplication via the activation of PR proteins. Constitutive expression of AtCBF1 in tomato resulted in a dwarf phenotype that was alleviated by the application of GA 3 (Hsieh et al, 2002a(Hsieh et al, , 2002b. To test whether GA 3 is a common antagonist of the AtCBF network that not only restores the dwarf and lateflowering phenotype but also influences the expression of the PR genes, we examined the expression levels of PR genes in AtCBF1 transgenic lines (C5, C15, and C21) and wild-type plants in the presence and absence of GA 3 treatment by northern-blot analyses (Fig.…”
Section: Progression Of Bw Is Delayed In Transgenic Atcbf1mentioning
confidence: 99%
See 1 more Smart Citation
“…One of these properties is reduced water deficit stress [25], which could allow cultivation on currently marginal land that meets tomato-production conditions in other respects. Conversely, it reduces the opportunity costs of growing tomato, as less water may be needed in the cultivation process.…”
Section: Tomatomentioning
confidence: 99%